2022
DOI: 10.3389/fonc.2022.964605
|View full text |Cite
|
Sign up to set email alerts
|

Invasive ductal breast cancer molecular subtype prediction by MRI radiomic and clinical features based on machine learning

Abstract: BackgroundMost studies of molecular subtype prediction in breast cancer were mainly based on two-dimensional MRI images, the predictive value of three-dimensional volumetric features from dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) for predicting breast cancer molecular subtypes has not been thoroughly investigated. This study aimed to look into the role of features derived from DCE-MRI and how they could be combined with clinical data to predict invasive ductal breast cancer molecular subty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…[ 24 , 35 ] To obtain the best prediction model, some scholars have compared the prediction performances of different ML algorithms. [ 24 , 35 , 46 ] Zhang [ 35 ] developed 5 ML models based on the radiomic features of dynamic contrast-enhanced MRI and non-mono-exponential model-based diffusion-weighted imaging to predict HER2+ and HER2− status, including LR, RF, AB, SVM, and LDA. Their findings revealed that both the RF and AB models exhibited superior predictive abilities compared to the other 3 models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 24 , 35 ] To obtain the best prediction model, some scholars have compared the prediction performances of different ML algorithms. [ 24 , 35 , 46 ] Zhang [ 35 ] developed 5 ML models based on the radiomic features of dynamic contrast-enhanced MRI and non-mono-exponential model-based diffusion-weighted imaging to predict HER2+ and HER2− status, including LR, RF, AB, SVM, and LDA. Their findings revealed that both the RF and AB models exhibited superior predictive abilities compared to the other 3 models.…”
Section: Discussionmentioning
confidence: 99%
“…Their findings revealed that both the RF and AB models exhibited superior predictive abilities compared to the other 3 models. Similarly, Sheng et al [ 46 ] found that the RF model outperformed other ML models by extracting radiomic features from dynamic contrast-enhanced-MRI to predict HER2-overexpressed and non-HER2-overexpressed BC.…”
Section: Discussionmentioning
confidence: 99%
“…These features were selected based on correlation. Sheng et al (33) combined dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) three-dimensional volume characteristics with clinical data to predict molecular subtypes of invasive ductal breast cancer using t tests and LASSO regression in R language for screening. The final features included shape-based features, texture features, wavelet features, first-order statistical features and the Laplacian of a Gaussian filter.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been estimated that around 50–70% of MRI findings requiring biopsy turn out to be non-cancer cases [ 5 ]. In recent years, radiomics and artificial intelligence have been increasingly applied in breast MRI [ 6 ], not only to classify breast lesions or predict response to treatment but also to differentiate benign from malignant lesions [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. Indeed, radiological practice includes a qualitative and subjective evaluation of the visible lesion describing different characteristics of the tumor aspect (e.g., the presence of spiculations and the presence of necrosis and microcalcifications).…”
Section: Introductionmentioning
confidence: 99%